Dynamics of travel decision-making between organized packaged tourists and backpackers - Wickrama Hewage, Thejani Madhuhansi; `K.P, Lalith Chandralal (International Journal of Applied Sciences in Tourism and Events, 2023)
Tourists are different in terms of their purpose of travel, the tourist type, the number of days spent, and how they spend time in a destination. Tourist decision-making models attempt to conceptualize how tourists make decisions during their pre-travel, onsite experiences, and post-travel stages. These models, including the grand models of tourist behavior, have paved the way to broaden our understanding of this complex behavioral phenomenon. Despite their remarkable contributions to the existing knowledge, these models display some limitations in terms of complexity, general nature of explanations, poor empirical support, and lack of consideration of different traveler types. Further examinations are necessary to understand the dynamic nature of decisions that take place under each broader stage. This study attempted to address some of these limitations through a qualitative inquiry with a comparison of tourist decision-making between two mainstream traveler types i.e. organized package tourists and backpackers.  The findings uncovered empirical evidence to propose a research proposition that a general travel decision-making model cannot be derived for different traveler types and certain alterations need to be done with reference to different traveler types. These findings contribute to the literature on tourist behavior by inviting scholars to revisit the existing models in light of different traveler types.